Pengendalian Larva Oryctes Rhinoceros Mengunakan Alat Modifikasi Tojok Injeksi Di Perkebunan Kelapa Sawit Di Kalimantan Barat - Ilham Hasbaini Rosid; Ribka Mayaninta; Octo Simanjuntak; Melya Shara; Yanse Masliana Pakpahan; Rohmat Hidayah (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Oil palm (Elaeis guineensis) is one of the most economically important plantation crops in Indonesia. Among the various pests that attack this plant, Oryctes rhinoceros is one of the most significant. Control efforts are generally focused on the adult stage using sex pheromones and on the larval stage through manual collection. In this study, a modified injection tool was used to apply insecticides directly into piles of empty fruit bunches (EFB). This tool enables chemical compounds to penetrate deeper into the organic material layers to effectively target and kill larvae. The results of the study showed that the use of acephate as the active ingredient provided better effectiveness compared with other tested insecticidal active ingredients.